Death from failed protection?: an evolutionary-developmental theory of Sudden Infant Death Syndrome - Renz-Polster, Herbert; Blair, Peter S.; Ball, Helen L.; Jenni, Oskar; Bock, Freia de (Human nature, 2024)
Sudden infant death syndrome (SIDS) has been mainly described from a risk perspective, with a focus on endogenous, exogenous, and temporal risk factors that can interact to facilitate lethal outcomes. Here we discuss the limitations that this risk-based paradigm may have, using two of the major risk factors for SIDS, prone sleep position and bed-sharing, as examples. Based on a multipronged theoretical model encompassing evolutionary theory, developmental biology, and cultural mismatch theory, we conceptualize the vulnerability to SIDS as an imbalance between current physiologic-regulatory demands and current protective abilities on the part of the infant. From this understanding, SIDS appears as a developmental condition in which competencies relevant to self-protection fail to develop appropriately in the future victims. Since all of the protective resources in question are bound to emerge during normal infant development, we contend that SIDS may reflect an evolutionary mismatch situation—a constellation in which certain modern developmental influences may overextend the child’s adaptive (evolutionary) repertoire. We thus argue that SIDS may be better understood if the focus on risk factors is complemented by a deeper appreciation of the protective resources that human infants acquire during their normal development. We extensively analyze this evolutionary-developmental theory against the body of epidemiological and experimental evidence in SIDS research and thereby also address the as-of-yet unresolved question of why breastfeeding may be protective against SIDS.